Cancer prevalence, incidence and mortality rates in Pakistan in 2012 - Muhammad Rehan Sarwar; Anum Saqib (Cogent Medicine, 2017)
According to estimates from the International Agency for Research on Cancer (IARC), there were 14.1 million new cancer cases and 8.2 million cancer deaths in 2012 worldwide. In this article, we provide an overview of the cancer burden in Pakistan, including the 1, 3, 5-years prevalence, estimated number of new cancer cases and deaths in 2012 by age. Data from GLOBOCAN 2012, produced by the IARC, were used. GLOBOCAN provides estimates of cancer prevalence, incidence and mortality worldwide, and for countries and regions. This article concluded that the most prevalent cancers in Pakistan include breast, lip and oral cavity, cervix uteri, colorectum and bladder, respectively. The cancers responsible for the highest incidence in both the genders (total = 148,041) in Pakistani population includes breast (n = 34038, 23%), lip and oral cavity (n = 12761, 8.6%), lung (n = 6800, 4.6%), non-hodgkin lymphoma (n = 5964, 4%) and colorectum (n = 5335, 3.6%), respectively. Whereas, the cancers responsible for the highest deaths (total = 101,113) in Pakistani population includes breast (n = 16232, 16.1%), lip and oral cavity (n = 7266, 7.2%), lung (n = 6013, 5.9%), oesophagus (n = 4748, 4.7%) and non-hodgkin lymphoma (n = 4374, 4.3%), respectively.